Geometry of large normal fault growth and linkage with temporal constraints: a case study on the Lanliao fault in Dongpu Sag, Bohai Bay basin, NE China - Xu, Han; Qiu, Liang; Yan, Dan-Ping; Wang, Xin-Wen (Frontiers in Earth Science, 2024)
The Dongpu sag exhibits highly representative structural features of the Bohai Bay sasin. By utilizing TDQ technology, geological profiles were generated through the processing of seismic data with a velocity model. These profiles were integrated to investigate the linkage geometry and timing of the Lanliao fault, the eastern boundary fault of the Dongpu sag. Structural analysis revealed at least five original fault segments of the Lanliao fault, each initiating independently during the early growth phase. The development of these isolated fault segments began in the early Eocene, concurrent with the deposition of the Es4 member. The southern fault segments were active earlier but became inactive later as the northern segments gained activity during the Es3 member. Transverse anticlines separate the northern and southern faults.By the time of the Es2 member, all segments had linked, forming a continuous boundary fault across the transverse anticlines. As the Dongpu sag expanded, the depocenter relocated. The southern fault formed a graben, known as the Gegangji subsag, controlling the depocenter during the Es3 3 and Es3 2 members. The depocenter of the Es3 1 member shifted northward swiftly, developing into a half-graben depocenter called the Huzhuangji subsag. In the post-linkage development phase, the activity of the Lanliao fault decreased over time, with displacement becoming more concentrated on the Huanghe fault, an intrabasin fault. The Huanghe fault then dominated basin sedimentation, moving the depocenter to the Mengmangji subsag.This study demonstrates that fault linkage is a significant event in basin evolution, exerting considerable control over sedimentation and the overall evolution of the basin.